2013
DOI: 10.1371/journal.pone.0066119
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immune-Related Proteins are Differentially Expressed during Hibernation in the American Black Bear

Abstract: Hibernation is an adaptation to conserve energy in the face of extreme environmental conditions and low food availability that has risen in several animal phyla. This phenomenon is characterized by reduced metabolic rate (∼25% of the active basal metabolic rate in hibernating bears) and energy demand, while other physiological adjustments are far from clear. The profiling of the serum proteome of the American black bear (Ursus americanus) may reveal specific proteins that are differentially modulated by hibern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 61 publications
2
24
1
Order By: Relevance
“…For example, we found that immunoglobulin heavy chain (a large polypeptide subunit of an antibody) was higher in bone samples in hibernating compared with active marmots. This is consistent with previous studies showing higher levels of immunoglobulin heavy chain in serum from hibernating compared with active bears (Chow et al 2013), which may possibly help explain bears' ability for wound healing during hibernation (Nishio et al 2009;Iaizzo et al 2012). Our finding is also consistent with increased numbers of B-lymphocytes in blood of hibernating 13-lined ground squirrels compared with active squirrels (Bouma et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…For example, we found that immunoglobulin heavy chain (a large polypeptide subunit of an antibody) was higher in bone samples in hibernating compared with active marmots. This is consistent with previous studies showing higher levels of immunoglobulin heavy chain in serum from hibernating compared with active bears (Chow et al 2013), which may possibly help explain bears' ability for wound healing during hibernation (Nishio et al 2009;Iaizzo et al 2012). Our finding is also consistent with increased numbers of B-lymphocytes in blood of hibernating 13-lined ground squirrels compared with active squirrels (Bouma et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study with a captive colony of dwarf lemurs, we found another iron‐related gene, haptoglobin to show extreme levels of expression during Torpor relative to an active state (fold change of 7.22; Faherty, Villanueva‐Cañas, et al., ). This gene was also shown to be highly expressed during Torpor in other hibernating species (Chow, Donahue, Vaughan, McConkey, & Vijayan, ; Mominoki, ; Mominoki et al., ; Vermillion, Jagtap, Johnson, Griffin, & Andrews, ; Yan, ).…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study with a captive colony of dwarf lemurs, we found another iron-related gene, haptoglobin to show extreme levels of expression during Torpor relative to an active state (fold change of 7.22 ;Faherty, Villanueva-Cañas, et al, 2016). This gene was also shown to be highly expressed during Torpor in other hibernating species (Chow, Donahue, Vaughan, McConkey, & Vijayan, 2013;Mominoki, 1998;Mominoki et al, 2005;Vermillion, Jagtap, Johnson, Griffin, & Andrews, 2015;Yan, 2006 (Utz & van Breukelen, 2013). Other studies have shown that rewarming rates for golden-mantled ground squirrels (Callospermophilus lateralis) can be nearly 1.5°C/min (Utz, Velickovska, Shmereva, & van Breukelen, 2007).…”
Section: Dwarf Lemurs Invest Much Energy Into Upregulation Of Iron mentioning
confidence: 84%
“…One explanation, revealed in previous research on brown bears (Ursus arctos), is that bears have more and smaller platelets compared with humans (Fröbert et al, 2010). Interestingly, other studies have demonstrated seasonal changes that may suggest modulation, including previous work done by Chow et al (2013) and Sheikh et al (2003) describing differences in immune-related proteins including alpha 2 macroglobulins.…”
Section: Introductionmentioning
confidence: 99%